2019
DOI: 10.1128/jvi.01834-18
|View full text |Cite
|
Sign up to set email alerts
|

Asparagine Is a Critical Limiting Metabolite for Vaccinia Virus Protein Synthesis during Glutamine Deprivation

Abstract: Viruses actively interact with host metabolism because viral replication relies on host cells to provide nutrients and energy. Vaccinia virus (VACV; the prototype poxvirus) prefers glutamine to glucose for efficient replication to the extent that VACV replication is hindered in glutamine-free medium. Remarkably, our data show that VACV replication can be fully rescued from glutamine depletion by asparagine supplementation. By global metabolic profiling, as well as genetic and chemical manipulation of the aspar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(57 citation statements)
references
References 61 publications
5
50
0
Order By: Relevance
“…It was released into the cell culture medium immediately after synthesis, which allowed it to be detected in real-time without the need to lyse the cells. Therefore, we used a reporter VACV, vLGluc, which was engineered to express Gluc in the WR strain of VACV under the control of a well-characterized viral late F17 promoter [ 20 ]. The luciferase expressed from this virus was found predominantly (99.8%) in the cell-culture medium.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was released into the cell culture medium immediately after synthesis, which allowed it to be detected in real-time without the need to lyse the cells. Therefore, we used a reporter VACV, vLGluc, which was engineered to express Gluc in the WR strain of VACV under the control of a well-characterized viral late F17 promoter [ 20 ]. The luciferase expressed from this virus was found predominantly (99.8%) in the cell-culture medium.…”
Section: Resultsmentioning
confidence: 99%
“…BS-C-1 cells (ATCC CCL-26) were purchased from ATCC and grown in Eagle’s Minimum Essential Medium (EMEM) supplemented as described above. The recombinant VACV—Western Reserve virus expressing Gluc under viral late promoter was described elsewhere, and it was a gift from Dr. Bernard Moss [ 20 ]. Wildtype and recombinant viruses were amplified in BS-C-1 cells, and they were cushion- and gradient-purified prior to use, as described elsewhere [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…These studies suggest that most glutamine-dependent protein translation activities can still proceed under asparagine supplementation in a glutamine-deprived environment, although the exact mechanism is still unknown. Furthermore, studies performed in endothelial cells, Kaposi's sarcoma-associated herpesvirus (KSHV)transformed cancer cells and several normal fibroblast or epithelial cell lines reported a similar effect of asparagine on supporting cell survival and protein translation after glutamine deprivation 44,49,50 . Interestingly, high intracellular asparagine levels have recently been identified to be essential for breast cancer metastasis 51 .…”
Section: Asparaginementioning
confidence: 98%
“…However, glutamine is also required for the de novo synthesis of asparagine by ASNS ( Figure 6A ). A recent study demonstrated that addition of asparagine could rescue vaccinia virus replication following glutamine deprivation (21). Therefore, we investigated whether loss of asparagine synthesis contributes to inhibition of HCMV replication following glutamine deprivation.…”
Section: Resultsmentioning
confidence: 99%
“…Despite ASNS knockdown, global proteins translation levels were maintained Furthermore, given the block in virus replication occurs relatively early in infection and knockdown cells could still fully support replication of HSV-1 and IAV, suggests the loss of replication is not simply due to loss of protein production, but rather indicates asparagine levels feed into a signalling pathway that influences replication of HCMV. While asparagine depletion had little effect on HSV-1 or IAV replication, a recent report demonstrated that, like HCMV, Vaccinia virus (VACV) is also highly dependent on asparagine levels and knockdown of ASNS resulted in attenuation of virus replication (21). Interestingly, despite the similar phenotype, there appears to be differences in the effects of asparagine depletion on the two viruses.…”
Section: Discussionmentioning
confidence: 99%